Analysis Of Vitamin C Levels Of Curry Leaf Ethanol Extract (Murraya Koenigii L. Spreng) By Uv-Vis Spectrophotometry - Iskandar, Sofyan Reza; Yuniarto, Prayoga Fery; Sulistyowati, Yuni (Al Makki Publisher, 2023)
Curry leaves (Murraya Koenigii L. Spreng) are a source of vitamin A, vitamin B, vitamin C, vitamin B2, calcium and iron in large quantities. Vitamin C serves to improve the body's immune system by stimulating the production of interferon (Winarsi, 2007). Determination of vitamin C levels in curry leaves (Murraya koenigii L. Spreng) has never been carried out so the following research was carried out to understand vitamin C levels for curry leaves (Murraya koenigii L. Spreng) by UV-Vis spectrometric method. The type of research applied is laboratory experiments. The population was curry leaves (Murraya koenigii L. Spreng) while samples were curry leaves (Murraya koenigii L. Spreng) which were dried in the sun and then extracted using 96% ethanol solvent. The results obtained with KMnO4 are positive, with iodine reagents being negative, and with ammonium molybdate being positive. Positive here means that vitamin C is obtained in the ethanol extract of curry leaves, and negative vice versa. Obtained an average vitamin C level of 3,962 ppm in curry leaf ethanol extract. It was concluded in this study that 96% ethanol extract in curry leaves contains vitamin C. And UV-Vis spectrophotometry succeeded in proving the levels of vitamin C contained in curry leaf plants.